A PRELIMINRY ANATOMICAL STUDY OF MALE REPRODUCTIVE SYSTEM OF THF FREHWATER CRAB POTAMON MAGUM MAGNUM (PRETZMAN) (ARTHROPODA: CRUSTACEA: DECAPODA) - SALIH, E. NABEEL; AL-BARWARY, H. T. I. BATOOL (The Bioscan, 2013)
The present study was conducted, as a preliminary study, on the male reproductive system of the freshwater crab Potamon magnum magnum, collected from the shores of river Tigris in Mosul City, Ninevah Province, Iraq, aiming at describing the male reproductive system which seems to have never been described before. Results of the present study showed that the male reproductive system consists of a pair of testes, a pair of vas deferens, ending into ejaculatory ducts and a pair of penises. Gonopods are also present which are known to serve as copulatory organs which transfer the spermatophores into female gonopores. The macroscopic anatomy of the testes showed a similar pattern to that described in other decapod species, e.g. in the paired testes, the H-like appearance and presence of gonopods.